Comparison of Arctic and Antarctic Stratospheric Climates in Chemistry Versus No‐Chemistry Climate Models. Issue 20 (22nd October 2022) - Morgenstern, Olaf; Kinnison, Douglas E.; Mills, Michael; Michou, Martine; Horowitz, Larry W.; Lin, Pu; Deushi, Makoto; Yoshida, Kohei; O'Connor, Fiona M.; Tang, Yongming; Abraham, N. Luke; Keeble, James; et al.
Abstract: Using nine chemistry‐climate and eight associated no‐chemistry models, we investigate the persistence and timing of cold episodes occurring in the Arctic and Antarctic stratosphere during the period 1980–2014. We find systematic differences in behavior between members of these model pairs. In a first group of chemistry models whose dynamical configurations mirror their no‐chemistry counterparts, we find an increased persistence of such cold polar vortices, such that these cold episodes often start earlier and last longer, relative to the times of occurrence of the lowest temperatures. Also the date of occurrence of the lowest temperatures, both in the Arctic and the Antarctic, is often delayed by 1–3 weeks in chemistry models, versus their no‐chemistry counterparts. This behavior exacerbates a widespread problem occurring in most or all models, a delayed occurrence, in the median, of the most anomalously cold day during such cold winters. In a second group of model pairs there are differences beyond just ozone chemistry. In particular, here the chemistry models feature more levels in the stratosphere, a raised model top, and differences in non‐orographic gravity wave drag versus their no‐chemistry counterparts. Such additional dynamical differences can completely mask the above influence of ozone chemistry. The results point toward a need to retune chemistry‐climate models versus their no‐chemistry counterparts. Plain Language Summary: Ozone is a chemical constituent of the atmosphere acting as an absorber of both solar ultraviolet light and infrared radiation emitted by the Earth. It therefore needs to be considered in climate models. Explicit ozone chemistry is a computationally challenging addition to a climate model; hence in most cases ozone is simply prescribed. Especially during relatively cold stratospheric winter/spring seasons, Antarctic and Arctic ozone depletion can be considerable. Such anomalous ozone loss is not reflected in the imposed ozone field, and hence differences in behavior are expected for such situations between chemistry‐ and no‐chemistry models. Indeed for such cold winters/springs, we find an enhanced persistence of such cold spells in a set of chemistry‐climate models, versus their no‐chemistry counterparts; such enhanced persistence generally makes the chemistry model less realistic than its no‐chemistry counterpart. However, if there are substantial further differences between the members of these model pairs, such as regarding their grid configuration or physical processes beyond chemistry, these can obscure the effect of ozone chemistry. We thus claim that adding stratospheric ozone chemistry to a climate model necessitates retuning to counteract a deterioration of the simulated stratospheric climate that can otherwise occur. Key Points: Coupling in ozone chemistry causes an increase in persistence of low temperature anomalies over both poles In the Antarctic, coupling in chemistry amplifies pre‐existing stratospheric cold biases These effects can be masked by other dynamical differences present in some models